2008
DOI: 10.1175/2007jhm924.1
|View full text |Cite
|
Sign up to set email alerts
|

Raindrop Size Distributions and Rain Characteristics in California Coastal Rainfall for Periods with and without a Radar Bright Band

Abstract: Recent studies using vertically pointing S-band profiling radars showed that coastal winter storms in California and Oregon frequently do not display a melting-layer radar bright band and inferred that these nonbrightband (NBB) periods are characterized by raindrop size spectra that differ markedly from those of brightband (BB) periods. Two coastal sites in northern California were revisited in the winter of 2003/04 in this study, which extends the earlier work by augmenting the profiling radar observations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
105
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 29 publications
17
105
2
Order By: Relevance
“…Echo-top heights derived from S-PROF radar reflectivity profiles are available for selected CZD and ATA events and are provided in the Supplementary File. Previous work (Martner et al, 2008) indicated that the mean echo-top height was higher (6.8 km, corresponding to (26.3 8C) for BB periods and lower (3.6 km, corresponding to (5.6 8C) for NBB periods, in accord with HR periods being colder with lower d . HRperiod echo-top heights are greater on average than those of LR periods, and the average BB height (height of maximum radar reflectivity) represents the freezing level and was 2.31 km above mean sea level.…”
Section: Rainfall Rate Accumulated Rainfall and Hydrogen Isotopic Comentioning
confidence: 77%
See 3 more Smart Citations
“…Echo-top heights derived from S-PROF radar reflectivity profiles are available for selected CZD and ATA events and are provided in the Supplementary File. Previous work (Martner et al, 2008) indicated that the mean echo-top height was higher (6.8 km, corresponding to (26.3 8C) for BB periods and lower (3.6 km, corresponding to (5.6 8C) for NBB periods, in accord with HR periods being colder with lower d . HRperiod echo-top heights are greater on average than those of LR periods, and the average BB height (height of maximum radar reflectivity) represents the freezing level and was 2.31 km above mean sea level.…”
Section: Rainfall Rate Accumulated Rainfall and Hydrogen Isotopic Comentioning
confidence: 77%
“…Figure 18 shows the strong correlation between mean echo-top heights of HR and LR periods and minimum d 2 H VSMOW of values of rainfall for 23 events having echotop data. Because BB rainfall has higher mean echo-top heights than NBB rainfall (Martner et al, 2008), we anticipate that there may be a correlation between intervals having precipitation categorised by S-Prof radar as BB rain and intervals categorised as HR periods using algorithmicisotopic categorisation of precipitation. Similarly, we anticipate that there may be a correlation between intervals having precipitation objectively categorised as NBB rain and periods categorised as LH periods.…”
Section: Potential For Improving Hydrograph Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…This data set is the same one used in the companion paper "Skewness as measure of the invariance of instantaneous renormalized drop diameter distributions -Part 1: Convective vs. stratiform precipitation" (Ignaccolo and De Michele, 2012). Bodega Bay is located on the coast of California, for extensive period of times (White at al., 2003;Martner et al, 2008). During these time intervals, precipitation "is primarily the result of orographically forced condensation and coalescence processes" (Martner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%